Invariant states for time dynamics of one-dimensional lattice quantum fermi systems (1991)
A problem of describing a set of time-invariant states for dynamics corresponding to a Hamiltonian H0 of a one-dimensional lattice quantum Fermi system is investigated. Assuming that an invariant state ? is the KMS-state for some 'Hamiltonian' H it is checked that H is proportional to H0, i.e., that ? is the KMS-state for ?H0. Thereby any 'natural' invariant state is the equilibrium Gibbs state in the situation under consideration. In is used an assumption that H0 is not quadratic form in creation and annihilation operators: in the latter case time-dynamics admits essentially more wide set of invariant states